A review of a study on improving the performance of spherical solar stills - Faiz Jodah; Wissam ِAlawee; Hayder Dhahad; Z.M. Omara (Engineering and Technology Journal)
The urgent need for potable water has increased despite water covering much of the Earth's surface. Solar desalination, which uses solar energy to produce fresh water, is an eco-friendly and cost-effective solution, especially for remote areas lacking clean drinking water. This technology is valuable even in deserts with no other freshwater sources. However, conventional solar stills have low efficiency. To address this, various experiments have been conducted to enhance the daily output of solar stills by improving evaporation and condensation rates, which standard distillers cannot achieve. This innovation in using solar power thus finds its place even on desert sands where no other freshwater source is available, demonstrating the immense value of harnessing solar energy for such an important purpose as providing fresh water. This article reviews the latest techniques to boost water productivity and improve various solar distiller designs' overall performance and thermal efficiency. It concluded with recommendations for future research, highlighting strategies that showed significant promise. The combination of flat plate collectors with spherical solar stills was the most efficient, achieving a productivity level of 7620 ml/m2/day. 57% increase due to the unique conditions created by rotating balls within the still. These findings underscore the potential of innovative design enhancements to improve desalination systems using solar energy significantly, and they encourage further research and development in this field.